Dynamic simulation of cable-stayed bridge [compact disc] - 455654 Pang, Eng Leong (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2006